Socio-Economic Analysis and Ownership of Health Insurance in the Utilization of Health Facilities for Elderly with Hypertension - Adila Solida; Dwi Noerjoedianto; Merliana Marbun (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2023)
Hypertension is the most common occurrence for the elderly in Jambi City with an increasing trend in the last three years. However, the utilization of health facilities, especially for outpatient hypertension, has had its ups and downs. This study aims to analyze the effect of socioeconomic, and insurance ownership on the utilization of health facilities for outpatient hypertension in the work area of Simpang IV Sipin Health Center Jambi City in 2022. This study is a quantitative study using a cross-sectional design. The sample amounted to 110 respondents who were selected using accidental sampling technique. The instrument used is a questionnaire. Data processing using statistical software with univariate analysis stage, bivariate analysis with chi-square test, and multivariate analysis with multiple logistic regression test. The results of the study show that there is an effect of employment status, income, costs and ownership of health insurance on the utilization of health facilities for the elderly with hypertension in Jambi City in 2022. The conclusion of the study is that income and ownership of health insurance are the main triggers that affect the use of health facilities for outpatient treatment elderly with hypertension in Jambi City.